2017
DOI: 10.1186/s11671-017-1914-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copper and Selenium Nanocarboxylates on Biomass Accumulation and Photosynthetic Energy Transduction Efficiency of the Green Algae Chlorella Vulgaris

Abstract: Nanoaquachelates, the nanoparticles with the molecules of water and/or carboxylic acids as ligands, are used in many fields of biotechnology. Ultra-pure nanocarboxylates of microelements are the materials of spatial perspective. In the present work, the effects of copper and selenium nanoaquachelates carboxylated with citric acid on biomass accumulation of the green algae Chlorella vulgaris were examined. Besides, the efficiency of the reactions of the light stage of photosynthesis was estimated by measuring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The hormetic phenomenon described by Zhu et al [ 23 ] was also confirmed by the results obtained with Cu nano-aquachelates carboxylated with citric acid on the biomass accumulation of the green algae Chlorella vulgaris [ 24 ]. This latter finding may be dependent on the increase in inorganic copper concentration which may impair biochemical and physiological processes in algal cells.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The hormetic phenomenon described by Zhu et al [ 23 ] was also confirmed by the results obtained with Cu nano-aquachelates carboxylated with citric acid on the biomass accumulation of the green algae Chlorella vulgaris [ 24 ]. This latter finding may be dependent on the increase in inorganic copper concentration which may impair biochemical and physiological processes in algal cells.…”
Section: Resultsmentioning
confidence: 54%
“…For example, stimulatory action of Ag-NPs was greater for NP formulations with a smaller diameter in human cell [ 12 ], plant [ 26 ] and larval models [ 34 ], than for NPs with a greater size [ 13 ]. Therefore, it can be speculated that factors other than size, including the original state of the material, e.g., powder vs. colloidal dispersion [ 12 ], the NP chemical composition [ 14 , 16 , 23 , 24 ] ( Figure 4 ), the agglomeration status [ 12 ], and ENM surface functionalization [ 13 , 16 , 26 ] ( Figure 4 ), should be considered as possible key factors in the hormetic response to NP insults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous reports [8,30], treatments with Cu 2+ depressed cell growth and decreased contents of photosynthetic pigments (chl-a, car or chl-b) in S. quadricauda and S. acutus, demonstrating that high levels of Cu 2+ triggered severe environmental concerns. A high level of Cu 2+ blocked the electron transport and subsequently inhibited PSII activity [31], which further decreased F ν /F m and adversely affected photosynthesis of algae [31][32][33][34][35]. In the present study, treatments with high levels of Cu 2+ decreased contents of photosynthetic pigments, rETR max and I k in both S. quadricauda and S. acutus, suggesting that the photosynthetic process was inhibited.…”
Section: Discussionsupporting
confidence: 42%
“…Previous studies have reported that Cu is an essential nutrient to nearly all species from animal to algae [15,16]. However, high concentration of Cu in water environment may result in toxicity to aquatic organisms [17]. In addition, Cu can generate various toxic effects on different aquatic species [18].…”
Section: Algal Growthmentioning
confidence: 99%